Influence of peat-derived humic acid on the growth of agarwood seedlings - Abdullah, Halimatul Sa’adiah; Kasim, Susilawati; Raguraj, Sriharan; Abdul Azim, Amir Affan; Mohd Amin, Adibah (Taylor and Francis Ltd., 2024)
Humic acid (HA) is widely used in agriculture as a biostimulant to enhance plant growth and nutrient uptake. Studies on the early growth promotion of agarwood seedlings using plant biostimulants have not been explored. Therefore, the objective of this study was to extract and characterize peat-derived HA and to determine the optimum rate that would exert biostimulant action on the early growth of agarwood seedlings at the nursery stage. HA was extracted from peat soil using a modified rapid alkaline hydrolysis method. Produced peat humic acid (PHA) was compared with commercial humic acid (CHA) for its chemical and spectroscopic characteristics. One-month-old agarwood seedlings were treated with PHA at different rates (0, 20, 40, 80, 160 and 320 mg kg−1) before the commencement of the experiment. The study was conducted for four months. The C/N ratio of both PHA and CHA were 25.85 and 26.93, respectively. Scanning electron microscope (SEM) and fourier-transform infrared spectroscopy (FTIR) spectra observation reveals that PHA and CHA have similar surface morphology and functional groups respectively. Results revealed that agarwood seedlings treated with 80 mg kg−1 of PHA significantly increased the plant height, stem diameter, the number of leaves, leaf area, dry matter weight, N and P concentrations in plant tissues, and N, P and K uptakes. Based on the findings, incorporation of PHA at the rate of 80 mg kg−1 with planting medium could be used as an optimum rate to enhance the growth of agarwood seedlings in the nursery stage.